Scientometric analysis of domestic dissertation research, containing the category of «patriotic education» in their titles - P. P. Pivnenko; N. P. Vitenko (Вестник Майкопского государственного технологического университета, 2024)
The relevance of the research is due to the increased interest and need of specialists of various categories in studying the problems of patriotic education in the modern sociocultural situation. The problem of the research is to conduct a scientometric analysis of dissertation research containing the category «patriotic education» in their titles. The purpose of the research is to show the main directions of research activities to reveal the content of the main category – «patriotic education». The objectives of the study are to show the role of scientometric analysis as a quantitative assessment of the characteristics of dissertation research, the dynamics of presenting problems of patriotic education in the titles of dissertations, to draw conclusions for further study of this problem and to determine the possibilities of the direction of this work.The research methodology consisted of a set of methods of scientific knowledge: scientometric analysis, synthesis, generalization. The research results. The article, based on the scientometric method, has examined dissertation topics containing the category «patriotic education» in their titles, presented in the section «Authors’ abstracts of dissertations» of the Unified Electronic Resource of the Russian State Library, which has made it possible to record given semantic units of the studied scientific and pedagogical content and carry out their scientometric analysis, design of further relevant research. Key findings. Quantitative analysis and substantive content of the thematic clusters presented in the article allow us to conclude that the process is not intensive, orderly and methodologically supported, and requires further and comprehensive study in the theoretical, methodological and practice-oriented field.